Effect of Contact Conditions of Torsional Wave Elastographic Probe on Human Cervix. (29th November 2018) - Rus, G.; Riveiro, M.; Molina, F. S.
Abstract : There is a challenge in characterizing the soft tissue mechanical functionality in cylindrical geometries by current elastography techniques applied to small organs. Torsional waves are a type of shear elastic waves that propagate through soft tissue radially and in depth in a curled geometry, ideally suited to explore structures such as the cervix. Here, a sensor based on a novel arrangement of concentric sandwiches of piezo- and electromechanical elements is prototyped and tested to quantitatively assess stiffness in human cervix. The purpose is to determine the robustness of a torsional wave elastography (TWE) sensor prototype to quantify cervical stiffness, as a first step to validate a reliable measurement protocol using TWE. An array of tests designed to validate a set of hypothesis about the contact conditions were performed on up to 3 different nonpregnant voluntary women. The mechanical properties were reconstructed from the recorded TWE signals, and the outcomes were statistically analyzed to validate the contact condition hypothesis. The results suggest that, although future tests need to be performed to fully assess the repeatability and quality of the measurements, some characteristics of the measurement protocol become clear; in particular: ( 1 ) the use of speculum is recommended since it not only stabilizes the measurements, but also corrects and stabilizes the orientation of the cervical neck, and allows to visually verify the positioning and alignment of the probe, while not significantly increasing discomfort to women during this test; ( 2 ) the use of lubricant gel has no significant effect on the measurement quality; ( 3 ) 1cm off-centering from external cervical os is not acceptable; ( 4 ) a range of applied force between 500-2000 N does not significantly vary measurement signal quality, but the reconstructed value of the shear modulus does vary, probably due to its constitutive nonlinearity; ( 5 ) breathing movements affects measurements, but short duration of TWE pulse (0.3 s) allows to take measurements in apnea.